1994
DOI: 10.1111/j.1365-2109.1994.tb00732.x
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and genetic parameters of body and compositional traits in Arctic charr, Salvelinus alpinus (L.)

Abstract: Phenotypic and genetic parameters of body and compositional traits were estimated for a population consisting of 327 two-year-old Arctic charr, Salvelinus alpinus (L.), from 21 full-sib groups. Heritability estimates for body traits, such as fork length, gutted weight, condition factor and visceral weight, were all of intermediate magnitude (0-24-0-45). Heritabilities for carcass component traits, e.g. fat, protein, dry matter and astaxanthin contents, were low to medium (0-0-0-28). Genetic and phenotypic corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 21 publications
2
19
0
Order By: Relevance
“…Color and associated carotenoid use in O. nerka appear under additive genetic control as has been reported in several other salmonid species Naevdal 1984, 1988;Iwamoto et al 1990;Elvingson and Nilsson 1994;Withler and Beacham 1994). The similar and intermediate color of both immature (flesh) and mature (skin) reciprocal hybrids indicates maternal or sex-linked effects were not important.…”
Section: Proximate Basis Of Adaptive Genetic Divergence In Carotenoidsupporting
confidence: 54%
“…Color and associated carotenoid use in O. nerka appear under additive genetic control as has been reported in several other salmonid species Naevdal 1984, 1988;Iwamoto et al 1990;Elvingson and Nilsson 1994;Withler and Beacham 1994). The similar and intermediate color of both immature (flesh) and mature (skin) reciprocal hybrids indicates maternal or sex-linked effects were not important.…”
Section: Proximate Basis Of Adaptive Genetic Divergence In Carotenoidsupporting
confidence: 54%
“…Elvingson and Nilsson (1994) found that the largest genetic and environmental correlations are obtained between body weight and body length at 1.5-2.5 years. These correlations decreased as differences in weight and length increased with age.…”
Section: Discussionmentioning
confidence: 96%
“…Special efforts have been made in some generations to obtain data on flesh colour and other flesh quality parameters (for methods see Elvingson & Nilsson, 1994), mortalities following fungal infections (Nilsson, 1992b) and frequency of eye cataracts (Peuhkuri et al, 2009). Selection of parent fish has been based on individual and family merit for growth in each generation.…”
Section: Methodsmentioning
confidence: 99%
“…Heritability estimates and estimates of genetic correlations have been obtained for a number of compositional and body traits (Elvingson & Nilsson, 1994). Fat content, protein, and dry matter all showed low heritabilities, but a high and significant heritability (0.28) was obtained for flesh colour in terms of its astaxanthin content.…”
Section: Other Traitsmentioning
confidence: 99%
See 1 more Smart Citation